2020
DOI: 10.17712/nsj.2020.1.20190018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an educational intervention on knowledge and perception of individuals at risk for stroke in Tabuk, Saudi Arabia

Abstract: Forces Hospital, was designed to assess the knowledge of people who were at risk for stroke, before and after delivering educational content. This content comprised 4-minute face-to-face explanation by a trained educator, 99-second video clip and a short hand-out. The assessment was performed by administering a structured questionnaire. Results:A total of 313 people participated in this study. Before the intervention, 63.6% understood stroke to be due to a disturbance in blood flow resulting in loss of brain f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
(18 reference statements)
0
4
0
1
Order By: Relevance
“…[ 11 ] Hypertension was also the most known risk factor in an interventional study conducted in Saudi Arabia. [ 12 ] Pre-education, numbness or weakness of a part of the body was the most recognized symptom of stroke in the present study. Similar findings were observed in previous studies, [ 10 , 11 , 13 ] but the percentage was much higher.…”
Section: Discussionmentioning
confidence: 56%
“…[ 11 ] Hypertension was also the most known risk factor in an interventional study conducted in Saudi Arabia. [ 12 ] Pre-education, numbness or weakness of a part of the body was the most recognized symptom of stroke in the present study. Similar findings were observed in previous studies, [ 10 , 11 , 13 ] but the percentage was much higher.…”
Section: Discussionmentioning
confidence: 56%
“…Similarly, a systematic review in 2012 con rmed the value of video-based education in altering health behaviors, showing e cacy in promoting various health-related actions, including prostate cancer screening, sunscreen adherence, human immunode ciency virus (HIV) testing, and treatment adherence [23]. The literature focusing on stroke knowledge and awareness has also demonstrated positive outcomes [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…26 Also, these findings disagree with the study conducted in Tabuk, Saudi Arabia in 2020, which found that before the intervention of an educational program, participants had a poor knowledge score (63.6 percent) about the correct meaning of stroke. 27 . It's very essential for nurses to know what stroke is and what types there are because nurses are frontline when patients come to the health facility and should carry out a preliminary assessment for him.…”
Section: Discussionmentioning
confidence: 99%
“…30 32 Stroke can be a preventable and curable disease. 27 Nurses should encourage at-risk individuals to take preventive medications (such as lipid-lowering, anticoagulant, and antihypertensive medications) and to make lifestyle modifications. 33 Also, stroke risk screenings are a great way to lower stroke risk by identifying people or groups of people who are at high risk for stroke and educating patients and the general public about stroke recognition and prevention.…”
Section: Discussionmentioning
confidence: 99%